Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

If we are to find the distance between the points $P(0,0)$ and $Q(-2,-3)$, then we can use the Theorem of Pythagoras for this purpose.

$distance (P,Q) = \sqrt{(x_2 -x_1)^2 + (y_2 -y_1)^2}$

therefore, $distance (P,Q) = \sqrt{-5}$ But the answer is undefined. Is this answer and the reason correct?

share|cite|improve this question

You are calculating wrong:

$distance(P,Q) = \sqrt{(x_2 -x_1)^2 + (y_2 -y_1)^2}=\sqrt{((-2)^2+(-3)^2)}=\sqrt{(13)}$.

share|cite|improve this answer
oh yes! Sorry!! – Samama Fahim Apr 20 '13 at 17:48

You forgot to square. $d(P,Q) = \sqrt{(-2)^2+(-3)^2} = \sqrt{4+9} = \sqrt{13}$.

share|cite|improve this answer

It looks like you added the differences $(x_2 - x_1)$ and $(y_2 - y_1)$ without squaring them first!

So you want $$\operatorname {distance}(P, Q)=\sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} = \sqrt{(-2)^2 + (-3)^2} = \sqrt{4 + 9} = \sqrt{13}$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.